Greenhouse gas emissions of African Stargrass-based dairy systems under organic or inorganic fertilization regimes - Solano López, Marvin Jaroht (2026)
Background: Properly managed livestock operations play a significant role in reducing greenhouse gas emissions in agriculture. We assessed the effects of applying organic and inorganic fertilizers to African Stargrass pastures on greenhouse gas emissions. Methods: The study was conducted at the Dairy Research Station of the University of Costa Rica (May–November 2019 and 2021). Six fertilization treatments were evaluated under a randomized complete block design. Greenhouse gases included methane (CH4) and carbon dioxide (CO2) fluxesmeasured at ground level using static chambers, nitrous oxide (N2O) emissions calculated using IPCC factors, and simulated enteric methane emissions usingthe LIFE-SIM model, based on forage biomass and nutritive value. Results: CO2 emissions were numerically similar(p>0.05),with greater values in sulfur-coated urea (15,114kg ha−1) and lower in Azospirillum (13,799kg ha−1).Soil CH4 was significantly greater (p < 0.05) in ammonium nitrate (3.30kgha−1) with respect to sulfur-coated urea (1.37kg ha−1). Emission intensity wasnumerically greater in slurry (2.58kg CO2eq kg−1 DM), and lower values insulfur-coated urea (1.56kg CO2eq kg−1 DM). Conclusions: Although some significant differences were found for soilemissions, both CH4 and N2O were a small fraction of the emissions when totalized as CO2eq. The type of fertilizer applied to African Stargrass pastures influenced the emission intensity as a result of their impact on grass productivity. This study depicted the impact ofsoil and enteric emissions inpastures, providingan integrated approach for mitigation strategies to tackle emissions undertropical conditions.